Suicidal ideation is associated with nighttime wakefulness in a community sample - Tubbs, Andrew S (Sleep, 2020)
STUDY OBJECTIVES: Nocturnal wakefulness is a risk factor for suicide and suicidal ideation in clinical populations. However, these results have not been demonstrated in general community samples or compared to sleep duration or sleep quality. The present study explored how the timing of wakefulness was associated with suicidal ideation for weekdays and weekends. METHODS: Data were collected from 888 adults aged 22–60 as part of the Sleep and Healthy Activity, Diet, Environment, and Socialization study. Suicidal ideation was measured by the Patient Health Questionnaire-9, while timing of wakefulness was estimated from the Sleep Timing Questionnaire. Binomial logistic regressions estimated the association between nocturnal (11 pm–5 am) and morning (5 am–11 am) wakefulness and suicidal ideation. RESULTS: Nocturnal wakefulness was positively associated with suicidal ideation on weekdays (OR: 1.44 [1.28–1.64] per hour awake between 11:00 pm and 05:00 am, p < 0.0001) and weekends (OR: 1.22 [1.08–1.39], p = 0.0018). Morning wakefulness was negatively associated with suicidal ideation on weekdays (OR: 0.82 [0.72–0.92] per hour awake between 05:00 am and 11:00 am, p = 0.0008) and weekends (OR: 0.84 [0.75–0.94], p = 0.0035). These associations remained significant when adjusting for sociodemographic factors. Additionally, nocturnal wakefulness on weekdays was associated with suicidal ideation when accounting for insomnia, sleep duration, sleep quality, and chronotype (OR 1.25 [1.09–1.44] per hour awake, p = 0.002). CONCLUSION: Wakefulness at night was consistently associated with suicidal ideation. Additionally, morning wakefulness was negatively associated with suicidal ideation in some models. Although these findings are drawn from a non-clinical sample, larger longitudinal studies in the general population are needed to confirm these results.